INNOVATIVE MANAGEMENT OF OIL AND GAS SECTOR AS A FACTOR OF ECONOMIC DEVELOPMENT OF RK - Z.A. Baymagambetova; A.S. Doshan; T.K. Kuangalieva; D. Satenova; D.T. Bizhanov (Academic Journal of Physical and Chemical Sciences, 2019)
Prospects for the development of the oil and gas industry are associated with new directions in technological development, including the use of new principles for the development of complex oil fields. In the future, production combinations of a new type, energy-gas and gas-chemical, in which the fuel scheme for the use of hydrocarbon resources will be auxiliary and chemical-technological, the main, can become effective. As for the work to improve the mining complex, it should be based on a new mineral resource strategy. The actual problem of the complex use of hydrocarbons can be solved based on regional innovation systems and subject to the creation of alternative methods for processing raw materials, allowing reducing costs, intensifying basic operations, and expanding the range of products. The republic has a huge potential of research and innovation projects, the practical implementation of which could significantly change the nature of its productive forces.